PÅ GENBESØG I MAGISKE VERDENER: Et essay - Sjørslev, Inger (Tidsskriftet Antropologi, 2010)
In classical anthropological literature, magic has been dealt with as technologies that are related to uncertainty and control. The present essay sets out from these themes, but argues that a theory of magic, as well, has to look at the triangle between matter or substance, form and holistic images, and techniques and actions. The incentive to discuss magic in the light of newer anthropological theory of materiality derives from a visit to the exhibition at the Tropenmuseum in Amsterdam: Vodou – a way of life. On the basis of impressions from this exhibition, particularly the encounter with the figures of the bizango spirits, the article suggests that magic has to do with materiality in ways that can be further illuminated by a closer attention to fetish and to sacrifice. The elaboration of materiality into different forms is salient in both of these phenomena. Magic, then, has to do with the shaping of matter, whether in form of packages where the substance of content may be of significance, or in the form of destruction. Keywords: materiality, structuring, technique, fetich, sacrifice, voodoo.